Pengembangan Sistem Monitoring Akademik dan Administrasi Siswa Pada Paud ABC - Jefry Kalvin Simanjuntak; Fajar Pradana; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Early childhood education program is very important. PAUD ABC is one of the schools that provide education for early childhood. In the process of education, PAUD ABC uses a liaison book and report for giving an academic information and administration for parents. However, in it's use there are several problems make the use of the book becomes ineffective.On The developed system there will be included with some features that expected to be used to solve the problems. Features include such as status knowing if parents have read the information provided from the liaison book or not, notifications for parents to provide informaion, as well as giving report about student's learning process to parents everyday. System development starts with requirement analysis using prototyping approach where there will be four times repeating process, then continue with designing and implementation process. The system will be tested using whitebox and blackbox method, which from the results will be known that the functions or the whole system can run well.